2000
DOI: 10.1038/sj.onc.1203798
|View full text |Cite
|
Sign up to set email alerts
|

Functional consequences of tumorigenic missense mutations in the amino-terminal domain of Smad4

Abstract: Smads, the intracellular e ectors of transforming growth factor-b (TGF-b) family members, are somatically mutated at high frequency in particular types of human cancers. Certain of these mutations a ect the Smad amino-terminal domain, which, in the case of Smad3 and Smad4, binds DNA. We investigated the functional consequences of four missense mutations in the Smad4 amino-terminal domain found in human tumors. The mutant proteins were found to have impaired abilities to bind DNA although they were fully capabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
0
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(84 citation statements)
references
References 53 publications
5
76
0
3
Order By: Relevance
“…This conclusion is consistent with a previous report (Moren et al, 2000). However, the Smad4 R100T mutation causes destabilization and proteasomal degradation of Smad4 (Moren et al, 2000;Xu and Attisano, 2000), indicating that this mutation may alter the global conformation of the protein. This is also illustrated in Figure 5b.…”
Section: Smad4 R100 May Not Be Directly Involved In Nuclear Importsupporting
confidence: 82%
See 1 more Smart Citation
“…This conclusion is consistent with a previous report (Moren et al, 2000). However, the Smad4 R100T mutation causes destabilization and proteasomal degradation of Smad4 (Moren et al, 2000;Xu and Attisano, 2000), indicating that this mutation may alter the global conformation of the protein. This is also illustrated in Figure 5b.…”
Section: Smad4 R100 May Not Be Directly Involved In Nuclear Importsupporting
confidence: 82%
“…As shown by several previous studies, the NLSinhibitory effects of the R100T mutation is probably caused by a general disruption of the overall structural integrity of Smad4 (Shi et al, 1998;Moren et al, 2000;Xu and Attisano, 2000). Thus, we have not assigned a specific role to this residue in nuclear import.…”
Section: Smad4 Nls Resembles An Extended Bipartite Nlsmentioning
confidence: 97%
“…Deregulation of any of the above-mentioned proteins impacts on either normal embryonic development or, alternatively, on a pathogenic process of human disease. As already discussed above, the first demonstration of ubiquitination as a regulatory mechanism of TGFb pathways came from studies of Smad4 mutants in human tumors [90,91].…”
Section: Relevance Of Stability Regulation Of Tgfβ Pathway Componentsmentioning
confidence: 99%
“…There is more information regarding the poly-ubiquitination and proteasomal degradation of mutant versions of Smad2 and Smad4 that are abundant in various human tumors. Mutations in the N-terminal MH1 domain probably affect the critical folding of this domain, causing general instability of the protein and Ub-mediated proteasomal degradation [90,91]. Such mutations are R133C in Smad2 and L43S, G65V, R100T and P130S in Smad4.…”
Section: Relevance Of Stability Regulation Of Tgfβ Pathway Componentsmentioning
confidence: 99%
“…In acute myelogenous leukemia a missense mutation in the MH1 domain (P102L) and a frameshift mutation resulting in termination of the MH2 domain, cause rapid SCF βTrCP -mediated proteasomal degradation of Smad4 [87]. Smad4 point mutations identified in pancreatic (L43S and R100T) and colorectal (G65V and P130S) cancers have a higher affinity for the βTrCP F-box protein, and consequently also show enhanced SCF βTrCP -mediated polyubiquitination and degradation as compared to wild-type Smad4 [82,88,89]. Significantly, Liang et al demonstrated that R100T, G65V, and L43S mutations result in massive phosphorylation of Smad4 by JNK/p38 MAPK, causing an increased affinity of mutant Smad4 not only for βTrCP, but also for Skp2 [90].…”
Section: Interplay Of Smad4 Post-translational Modifications In Cancementioning
confidence: 99%